Answer:
(2 x - 3)^2 thus it's True
Step-by-step explanation:
Factor the following:
4 x^2 - 12 x + 9
Factor the quadratic 4 x^2 - 12 x + 9. The coefficient of x^2 is 4 and the constant term is 9. The product of 4 and 9 is 36. The factors of 36 which sum to -12 are -6 and -6. So 4 x^2 - 12 x + 9 = 4 x^2 - 6 x - 6 x + 9 = 2 x (2 x - 3) - 3 (2 x - 3):
2 x (2 x - 3) - 3 (2 x - 3)
Factor 2 x - 3 from 2 x (2 x - 3) - 3 (2 x - 3):
(2 x - 3) (2 x - 3)
(2 x - 3) (2 x - 3) = (2 x - 3)^2:
Answer: (2 x - 3)^2
Answer:
1. its substitution
2.
3. order of operations
4. variable
5. equation
Step-by-step explanation:
Answer:3.42
Step-by-step explanation:to get the answer to a area equation you need to multiply the length by the width.
The square root of four is two. To find the square root of four you find out what number, when multiplied by itself will get four. In this case, 2×2=4.
The ratio given says this - 3 puppies : 2 adults = 5 total dogs
You are given (?) puppies : (?) adults = 80 total dogs
In this case, you are trying to find the number of puppies, so you do not need to care about the number of adults. You need to compare the ratio with the actual amount.
Total/puppies = total/puppies
5/3 = 80/(?)
Now, cross multiply.
5(?) = 240
Divide both sides by 5 and you get your answer.
(?) = 48